(untitled) (Experimental biology, 2020)
Heavy metals (including mercury, lead, cadmium) and their compounds are the common and highly toxic substances that can accumulate in living organisms. Salts of heavy metals interact with the biological components of cells, having a significant impact on body functions. Inhibition of enzymes and irreversible conformational changes in macromolecules can lead to changes in a range of metabolic processes. Investigations of the lead acetate and mercury chloride effects on erythrocyte membranes resistance in vitro condition were carried out to value the potential pathophysiological role of heavy metals on the body and to find out the mechanism of isolated and combined action of toxicants. The study results have shown that lead acetate and mercury chloride dose-dependently reduce the osmotic and peroxide resistance of erythrocytes. It should be noted that the most significant effect on erythrocyte hemolysis is observed under the action of all concentrations of mercury chloride. Comparison of the erythrocyte membranes permeability under the action of lead acetate and mercury chloride increasing concentrations showed that both toxicants have a damaging effect on the state of erythrocyte membranes, which leads to a dose-dependent increase in hemolysis. High concentrations of lead acetate and mercury chloride, equal to 20.0 mm, cause the maximum hemolysis value of erythrocytes. The joint action of heavy metal ions on the state of erythrocyte membranes in vitro was accompanied by a decrease in the resistance of erythrocyte membranes. It is shown that the combined action of Pb2 + and Hg2 + ions effect significantly exceeds the values ​​obtained with their isolated effect. The results of our studies have shown that both isolated and combined action of heavy metal ions have an adverse effect on the erythrocyte membranes state. The results of our studies have shown that both isolated and combined action of heavy metal ions have an adverse effect on the erythrocyte membranes state. Key words: Heavy metals, resistance, hemolysis, erythrocytes